Studying the influence of the intensity of mechanochemical activation on the process of steam conversion of coal - Luhovskoi, Artur; Glikin, Marat; Kudryavtsev, Sergey; Glikina, Irene (Eastern-European Journal of Enterprise Technologies, 2018)
We continue to study the process of converting coal into synthesis-gas under conditions of aerosol nanocatalysis and reasonably expect would-be benefits of industrial technology. The advantages include a possibility to change the rate of reaction by influencing the intensity of mechanochemical activation of the catalyst. We investigated the process in a reactor where the mechanochemical activation is performed by the rotation of the catalytic system. The effect of activation intensity on chemical reactions under conditions of aerosol nanocatalysis has been proven earlier for the fluidized and vibro-liquefied layer of the catalytic system. Previous studies have shown that the mechanochemical activation affects the composition of conversion products, namely the ratio of СО:Н2. That would make it possible in the future to quickly reorient the production of synthesis-gas in line with the needs of market for organic products. The research results showed that at a temperature of 750 °C, 1 bar, MCA intensity of 2‒4 Hz and with an excess of coal (С:Н2О=5.5:1), the obtained ratio СО:Н2=1:1.99–1:.2,10 can be used for obtaining alcohols. At a temperature of 750 °C, 1 bar, MCA intensity of 0‒1 Hz and with an excess of coal (С:Н2О=5.5:1), the obtained ratio СО:Н2=1:1.19–1:1.35 can be applied for obtaining esters. We also noted the possibility of obtaining synthesis-gas with a ratio of 1:2.3 (2.5), which can be applied for obtaining hydrocarbons. This ratio was derived in the following mode: temperature 750 °C, pressure 1 bar, the ratio coal:water=1:0.87, MCA intensity 3‒4 Hz. The specified process to obtain hydrocarbons was investigated at 230 °C, 1 bar, in a vibro-liquefied layer of the catalyst aerosol at ratio СО:Н2=1:3 at 3 Hz and СО:Н2=1:2 at 3 and 5 Hz. The results of this paper are continuation of a global study into coal processing with obtaining the required industrial product. This special feature is the advantage of conducting a given process based on the aerosol nanocatalysis technology